2019
DOI: 10.1590/s0102-865020190060000009
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3 beta inhibitors protectagainst the acute lung injuries resulting from acute necrotizing pancreatitis

Abstract: Purpose The research is intended for clarification of the efficacy as well as the underlying mechanism of GSK-3β inhibitors on the advancement of acute lung injuries in acute necrotizing pancreatitis (ANP) in rats. Methods Seventy-two rats were randomly divided into 6 groups: (1)ANP-vehicle; (2)ANP-TDZD-8;(3)ANP-SB216763;(4)Sham-vehicle;(5)Sham-TDZD-8;(6)Sham-SB216763; Blood biochemical test, histopathological examination and immunohistochemical analysis of rats pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“… 19 In contrast, GSK-3β inhibitors decreased the activation of NF-κB, which in turn caused a decreased formation of inflammatory mediators. 20 , 21 Consistent with previous reports, our results indicated that inhibitors of GSK-3β can suppress NF-κB activation and IkB degradation in HBECs after PM2.5 treatment.…”
Section: Discussionsupporting
confidence: 92%
“… 19 In contrast, GSK-3β inhibitors decreased the activation of NF-κB, which in turn caused a decreased formation of inflammatory mediators. 20 , 21 Consistent with previous reports, our results indicated that inhibitors of GSK-3β can suppress NF-κB activation and IkB degradation in HBECs after PM2.5 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Our former research about the expression of GSK-3β in the acute edematous pancreatitis shows that both GSK-3βmRNA and protein expression level were associated with the severity of the disease (40). Also, Jin also found that the expression of GSK-3β is elevated in acute necrotizing pancreatitis) (41). It could be assumed that GSK-3β was activated in acute pancreatitis and was associated with the severity of the pancreatitis.…”
Section: Discussionmentioning
confidence: 94%
“…In order to relief ARDS, it appears a positive outcome by inhibition strategy of GSK3β through inhaling aerosolized insulin, [37]. In acute necrotizing pancreatitis (ANP)-elicited lung injury, protective effect of p-GSK3β (Ser9) exhibits by treatment of GSK3β inhibitors (TDZD-8 or SB216763) [38]. Since NF-κB could be phosphorylated by GSK3β and lead to transcriptional responses, inhibitors of GSK3β may decrease the activation of NF-κB and then reduce downstream gene expression (IL-1β, IL-6, and TNF-α) [29].…”
Section: Gsk3 In Acute Respiratory Distress Syndromementioning
confidence: 99%
“…1). Meanwhile, by applying GSK3β inhibitors (TDZD-8 and SB216763 pretreatment,1 mg/kg) to treat ANP rats, it is found that the increased expression of p-GSK3β (Ser9) and IL-10 levels in lung [38].…”
Section: Gsk3 In Acute Respiratory Distress Syndromementioning
confidence: 99%